2020
DOI: 10.3390/ijms21165769
|View full text |Cite
|
Sign up to set email alerts
|

Medaka (Oryzias latipes) Embryo as a Model for the Screening of Compounds That Counteract the Damage Induced by Ultraviolet and High-Energy Visible Light

Abstract: Continuous overexposure to sunlight increases its harmful effects on the skin. For this reason, there is a growing need to characterize economic models more representative of the negative effects and counteracting responses that irradiation causes on human skin. These models will serve for the screening of protective compounds against damage caused by ultraviolet (UV) and high energy visible light (HEV). Therefore, two common in vitro models employed for sunlight irradiation studies, namely human keratinocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Searches were restricted to clinical trials, systematic reviews, meta-analyses, and in vitro and in vivo studies reporting results in humans or non-clinical specimens. PubMed was searched using the term string (["blue light" OR "blue-light" OR "violet-blue light" OR "high-energy visible light"] AND [skin OR [8] 450 nm at 30 mW/cm 2 Mignon et al 2018 [9] 400-500 nm (peak at 450 nm) at 17.3 J/cm 2 for 6 h Morvan et al 2019 [10] ≥400 nm and ≥450 nm at 120, 150, and 200 J/cm 2 Mann et al 2019 [11] Reconstituted human epidermis 0.14% at 350-400 nm, 98.3% at 400-700 nm, 1.7% at 700-1,400 nm, and 0.3% at >1,400 nm at 65, 130, and 180 J/cm 2 Liebel et al 2012 [12] 445-465 nm at 50 J/cm 2 Merino et al 2020 [6] Volunteers 0.14% at 350-400 nm, 98.3% at 400-700 nm, 1.7% at 700-1,400 nm, and 0.3% at >1,400 nm; 50 J/ cm 2 at 150 mW/cm 2 Liebel et al 2012 [12] Artificially carbonylated porcine stratum corneum 470 nm at 12 J/cm 2 Yoo et al 2020 [17] Carotenoid degradation Volunteers 380-495 nm (peak at 440 nm) at 50 or 100 J/cm 2 Vandersee et al 2015 [18] 450±20 nm at 45 J/cm 2 for 5 consecutive days, 450±20 nm at 135 J/cm 2 single irradiation Schütz et al 2019 [19] 440 nm (peak) at 100 J/cm 2 Mann et al 2019 [11] Flavin degradation Hairless mice 460 nm (peak) at 44 mW/cm…”
Section: Search Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Searches were restricted to clinical trials, systematic reviews, meta-analyses, and in vitro and in vivo studies reporting results in humans or non-clinical specimens. PubMed was searched using the term string (["blue light" OR "blue-light" OR "violet-blue light" OR "high-energy visible light"] AND [skin OR [8] 450 nm at 30 mW/cm 2 Mignon et al 2018 [9] 400-500 nm (peak at 450 nm) at 17.3 J/cm 2 for 6 h Morvan et al 2019 [10] ≥400 nm and ≥450 nm at 120, 150, and 200 J/cm 2 Mann et al 2019 [11] Reconstituted human epidermis 0.14% at 350-400 nm, 98.3% at 400-700 nm, 1.7% at 700-1,400 nm, and 0.3% at >1,400 nm at 65, 130, and 180 J/cm 2 Liebel et al 2012 [12] 445-465 nm at 50 J/cm 2 Merino et al 2020 [6] Volunteers 0.14% at 350-400 nm, 98.3% at 400-700 nm, 1.7% at 700-1,400 nm, and 0.3% at >1,400 nm; 50 J/ cm 2 at 150 mW/cm 2 Liebel et al 2012 [12] Artificially carbonylated porcine stratum corneum 470 nm at 12 J/cm 2 Yoo et al 2020 [17] Carotenoid degradation Volunteers 380-495 nm (peak at 440 nm) at 50 or 100 J/cm 2 Vandersee et al 2015 [18] 450±20 nm at 45 J/cm 2 for 5 consecutive days, 450±20 nm at 135 J/cm 2 single irradiation Schütz et al 2019 [19] 440 nm (peak) at 100 J/cm 2 Mann et al 2019 [11] Flavin degradation Hairless mice 460 nm (peak) at 44 mW/cm…”
Section: Search Methodologymentioning
confidence: 99%
“…Multiple studies have shown that blue light exposure causes excessive ROS generation in cultured human keratinocytes and dermal fibroblasts, in medaka fish embryos, and in the skin of hairless mice and healthy human volunteers [6, 7, 9, 11-14, 16, 18-20]. The main chromophores responsible for blue light-induced ROS overproduction are believed to be flavins, such as flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN), and porphyrins such as heme [5].…”
Section: Introductionmentioning
confidence: 99%
“…OPN3 is a non-visual OPN that is highly expressed in the skin, and has been shown to upregulate tyrosinase activity in human epidermal melanocytes [23]. OPNs are chromophores responsible for the direct effects of blue light and their activation leads to an overproduction of ROS [24]. Lan et al demonstrated that OPN3 functions as a UVA phototransduction sensor in fibroblasts, playing a role in the upregulation of MMP-1 and MMP-3 expression [25].…”
Section: Introductionmentioning
confidence: 99%
“…This is because paddy fish have a fast growth rate, short lifespan, and life cycle, are easy to identify and cultivate and have a wide geographic distribution [9]- [12]. Not only in fish but embryos from paddy fish can also be used as ecotoxicological test biota [13]- [22]. One of the requirements as a test biota is that this paddy fish embryo has a sensitivity to various important contaminants such as xenobiotics [18], [23]- [25].…”
Section: Introductionmentioning
confidence: 99%